The Effect of An Educational Curriculum According to (K.W.L) Strategy on Some Mental Abilities and Learning Some Basic Football Skills for Students - Ali Mahdi Hassan1 , Yousef Abdul Karim Yousef Abu Ghneim2, Hayder Naji Habash Alshawi 3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research problem was centered in the fact that the student usually cares about playing without using themental abilities in the skill and what is known about the skill and what he wants to know and what he learnedfrom it, and through the experience of the researchers, they found that it is necessary to review the strategiesand methods of teaching used and the introduction of modern educational methods based on the needs ofstudents and their inclinations And their psychological desires and needs, and one of the most importantmodern strategies is the (KWL) strategy that works to stimulate students ’previous knowledge and make ita starting point for linking it with new information to renew the meaning of learning and increase studentconfidence and his ability to plan, monitor and strengthen He did his work, as well as developing mentalabilities that are one of the main goals in education, as traditional methods that focus on preserving andretrieving study material only do not necessarily lead to developing mental abilities, and that the researchproblem manifests itself in identifying the impact of using the KWL strategy in Some mental abilities,cognitive achievement, and learning some basic skills of football for students. The research objectives wereto prepare a teaching strategy (KWL) for students and to identify their effect on mental capabilities and insome basic skills for football for students. The researchers assumed that there were no significant differencesin Mental abilities and learn some basic football skills for students.